“Italian Theme” in Victorian Country House Architecture of England - Sokolova, Maria V. (Actual Problems of Theory and History of Art, 2016)
The article is devoted to the country house architecture of the Victorian era. The Victorian time is marked by the great variety of stylistic tendencies typical of the historicism period. Particularly significant is the turning to the national sources in search of the national style. There is another aspect of our research that has not been studied yet. It is the destiny of classical tradition at the epoch of historicism. Did it come to the end? Trying to answer this question, we tended to study the country house architecture of the Early Victorian period. We find that at this time the tendencies of the Georgian era, with their interest for classical heritage, were still rather strong. The greatest architect who built houses in classical taste for aristocratic estates was Ch. Barry. It was not only the aristocracy who often preferred the classical style, but there were some modest country estates also built in this manner. Classical heritage continued to play an important role in the architectural practice of the Victorian era.
Keywords: Victorian age; country house building; national style; classical tradition; English architecture; Ch. Barry